2018
DOI: 10.1021/acs.jpca.8b10286
|View full text |Cite
|
Sign up to set email alerts
|

1,2-H Atom Rearrangements in Benzyloxyl Radicals

Abstract: The rate constants for solvent-assisted 1,2-H atom rearrangements in para-substituted benzyloxyl radicals were studied with density functional theory. The rate of the radical rearrangement, calculated through transition state theory with Eckhart tunneling corrections, was shown to be drastically impacted by the presence of both implicit and explicit solvent molecules, with a quantitative agreement with laser flash photolysis studies for a variety of electron-donating and -withdrawing substituents. The rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Isomerization of the oxygen-centred radical to the carbon-centred radical through a formal 1,2-H shift is well documented and a recent theoretical study has revealed that water accelerates this process through a cyclic transition state involving two water molecules. 16 As shown in Fig. 1, in our case from radical INT-1 with two water molecules ( INT-1 ·2H 2 O), the cyclic transition state TS-1 ·2H 2 O with an activation barrier ΔΔ G of only +7.3 kcal mol −1 was found.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Isomerization of the oxygen-centred radical to the carbon-centred radical through a formal 1,2-H shift is well documented and a recent theoretical study has revealed that water accelerates this process through a cyclic transition state involving two water molecules. 16 As shown in Fig. 1, in our case from radical INT-1 with two water molecules ( INT-1 ·2H 2 O), the cyclic transition state TS-1 ·2H 2 O with an activation barrier ΔΔ G of only +7.3 kcal mol −1 was found.…”
Section: Resultssupporting
confidence: 54%
“…Isomerization of the oxygen-centred radical to the carboncentred radical through a formal 1,2-H shift is well documented and a recent theoretical study has revealed that water accelerates this process through a cyclic transition state involving two water molecules. 16 As shown in ΔΔG of only +7.3 kcal mol −1 was found. In contrast, a much higher activation energy (+23.9 kcal mol −1 ) is required for the 1,2-H shift of the isolated radical species (TS-1).…”
Section: Theoretical Studies For the Reaction Pathwaymentioning
confidence: 89%
“…The stabilization of the activation energy barrier for hydrogen transfer due to the solvent has been seen elsewhere for protic solvents. Additionally, the incorporation of additional solvent molecules, specifically for water, to assist the hydrogen transfer mechanism has been shown previously to further stabilize the transition state. Because DMSO is not a protic solvent and the hydrogens are nonacidic, this type of proton-assisted transfer is not favorable and the energy barrier for hydration increases to 62.4 kcal/mol (Figure f). The trend for the general lowering of TS energies for the protic solvent was also looked at with an implicit solvation of water and acetic acid, and the results are similar to that seen in the gas phase (Table S4).…”
Section: Resultsmentioning
confidence: 92%
“…Aside from the two pathways shown in Figure (radical recombination to yield PC4 vs. separation of the complex PC3 to form radicals 7 and 4 and water), additional reaction pathways are conceivable. This may, for example, include the water‐mediated isomerization of the benzyloxyl radical ( 4 ) to the hydroxybenzyl radical through a formal 1,2‐hydrogen shift (not shown) . The relevance of this pathway will, among other things, depend on the polarity of the surrounding solvent and its ability to engage in hydrogen‐bonding interactions with the radical 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This may,f or example, include the water-mediated isomerization of the benzyloxyl radical (4)t ot he hydroxybenzyl radical through af ormal 1,2-hydrogen shift (not shown). [43][44][45] The relevance of this pathway will, among other things,d epend on the polarity of the surrounding solventa nd its ability to engage in hydrogen-bonding interactions with the radical 4. [46][47][48][49][50] For the sake of completeness, it should also be mentioned that the toluenes hown in Figure 3a sa na ctive reaction partner can potentially also "solvate" the hydroperoxide 3 while it undergoes OÀOb ond homolysis and then react with the generated HOC radicali nas econd step along the lines shown in Figure 2.…”
Section: Reaction Of Benzylhydroperoxide With Toluenementioning
confidence: 99%